Understanding the aliya pulsed electric field dose-response relationship: Implications for ablation size, thermal load, and immune response in an orthotopic murine breast cancer model. - Ebtesam H O Nafie; Chiara Pastori; Rupsa Acharya; Rosa Kaviani; David Hunter; Waleed Shalaby; William S Krimsky; Robert E Neal (PLoS ONE)
Aliya®Pulsed Electric Field (PEF) technology is an emerging strategy in the field of cancer treatment, offering a novel approach to ablation therapy that does not rely on thermal mechanisms. By employing a multi-stage experimental setup, including potato tuber, porcine liver, and murine breast cancer models, we explored the dose-response relationship on ablation and immune modulation by varying the pulse packets delivered from 20 to 100. The biologic response observed with 60 packets represented a minimum effective dose yielding reproducible ablation parameters, immune response, and efficacy which could be augmented with immune checkpoint blockade. This pre-clinical analysis provides a first step toward understanding the therapeutic index for PEF technology beyond ablation, a consideration that will require robust clinical validation in well-designed prospective studies.